Development of a standardized and reproducible murine femoral distraction osteogenesis model - Yuejun Lin; Zhaowei Jiang; Jiaming Yang; Ming Wang; Haixing Wang; Xiaoting Zhang; Xuan Lu; Shanshan Bai; Tongzhou Liang; Botai Li; Jie Shao; Lu Zhang; et al. (Journal of Orthopaedic Translation)
Objective: Distraction osteogenesis (DO) has been widely used to treat bone defects as its effectiveness in bone regeneration. Currently, distraction devices for establishing DO models are mainly developed for rats or large animals. However, a mouse DO model is in great need for in-depth mechanistic investigations using various transgenic mice. The current study reports the development of a reproducible murine DO model. Methods: A mini-titanium lengthener was designed and fabricated. The mini-lengthener was applied on the murine femur with four threaded pins using a designed clamp as the drilling and insertion guide. After transverse osteotomy using a Gigli saw, and after 5 days of latency, DO procedures started at 0.3 mm/day for 10 days, and the consolidation period was left for 28 days. The bone formation was monitored by radiography and histology. Potential effects on animal locomotion during DO were also measured by behavior tests. Results: Separated bone segments maintained good alignment during the entire DO phases. New bone formation was found as early as the end of the distraction phase. Active bone remodeling was found between the separated bone segments at late distraction and early consolidation phases. At the mature consolidation phase, bone remodeling was mainly observed in the contact cortical bone. Mice underwent DO procedure did not have significant impairment in their locomotion. Conclusion: We have successfully developed a murine femoral DO model, which may be used to study the biological processes of DO. We also developed the mini-lengthener and the guide clamp to ensure the standardization and reproducibility of the mouse DO model.The translational potential of this article: Current study reports the development of a murine femoral DO model. A well-established murine DO model will facilitate further investigations of the biological mechanisms of DO in various transgenic and normal mice.